IMIPRAMINE INDUCED EXTRAPYRAMIDAL SYMPTOMS - Saha, Dr Amitabh; Duttta, Dr Bikram; Saini, Dr SK; Kumar, Dr Amit (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2018)
Extra pyramidal szymptoms are common side effets een with antipsychotics , however itsassociation with tricyclics is rare but seen in clinical practice.A patient with Moderate depressive episodewas managed with tricycyclic antidepressants. Patient developed acute dystonia on the third day andthere were no additional medications he was prescribed. Tricyclic antidepressant (TCA)-related extrapyramidal side effects have been reported but these side effects are not well known. The prevalenceand reporting of these side effects is low, despite widespread use of these medications. In some cases, ithas also been seen to disappear even though the same dose of TCA is continued, and they do not seemto be a drug class reaction. It is also possible that . .